Uma aplicação de painel dinâmico com variável Threshold para a proporção de pobres dos estados brasileiros - Matos, Samuel Saymon de Morais (2011)
The aim of this study is to investigate the convergence of poverty headcount poverty (P0) in nineteen Brazilian states plus the Federal District. To this end, adjustments have been made from two different models of per capita income in a dynamic panel. The first is a linear model developed by Evans and Karras (1996) and the second is a nonlinear model with the threshold variable of Beyaert and Camacho (2008). The selected states were Piauí, Maranhão, Ceara, Rio Grande do Norte, Paraíba, Pernambuco, Alagoas, Sergipe, Bahia, Minas Gerais, Espirito Santo, Rio de Janeiro, São Paulo, Paraná, Santa Catarina, Rio Grande do Sul, Goiás, Mato Grosso, Mato Grosso do Sul and the Federal District. To increase the efficiency of the tests and in order to find possible convergence clubs, the states have been divided in two groups: the non-Northeast and Northeast. According to the tests, neither the northeastern states converge nor does the group of other states converge. In both cases the linear model is preferred to non-linear. For the group with all the states, the non-linear model is the most suitable. The empirical results for this group concluded in favor of absolute convergence among selected states.